Pengaruh Penggunaan Iklan dan Brand Ambassador Terhadap Minat Beli Konsumen Pada Layanan Bimbel Online - Shendy Andrie Wijaya; Arie Eko Cahyono; Siti Ukrimatul Irhamniah (Universitas Negeri Surabaya, 2022)
This research was conducted 1) to determine the partially significant effect of advertising on consumer buying interest in online tutoring services at SMAN 3 Jember. 2) To find out the partially significant effect of brand ambassadors on consumer buying interest in online tutoring services at SMAN 3 Jember. 3) To determine the simultaneous significant effect of advertising and brand ambassadors on consumer buying interest in online tutoring services at SMAN 3 Jember. The population in this study were students of class X and XI at SMAN 3 Jember. The type of research used by the researcher is descriptive research using multiple linear regression analysis method with data processing using the SPSS 22 program. Hypothesis testing in this study uses t test and f test with a value level of a = 5%. The results of this study indicate that 1) partially advertising has a significant effect on consumer buying interest in online tutoring services at SMAN 3 Jember, while 2) brand ambassadors partially have no significant effect on consumer buying interest in online tutoring services at SMAN 3 Jember. 3) Simultaneously, advertising and brand ambassadors have a significant effect on consumer buying interest in online tutoring services at SMAN 3 Jember